Emergency preparedness for Small Modular Reactors (SMRs) : the case of Sweden - Thelander, Åsa ; 0000-0002-5000-542X; Ek, Åsa ; 0000-0002-2377-459X; Rääf, Christopher ; 0000-0002-9495-7166; Eriksson Stenström, Kristina; Rahm, Henrik (European Radiation Protection Week 2025, London, United Kingdom, 2025-09-29 - 2025-10-03, 2025)
Small modular reactors (SMRs) have become part of the solution for future fossil-free energy systems. Compared to traditional nuclear power plants (NPPs), risks are different and additional actors are involved. The aim of this paper is to analyse key actors’ understanding of emergency preparedness for SMRs in Sweden. Emergency preparedness is an active, continuous and integrated process involving abroad spectrum of actors. It is based on how actors make sense of this process and understand issues and events. Often it involves coordination and cooperation between organisations. Therefore, we ask 1) how key actors make sense of SMRs and their role in emergency preparedness and 2) How stakeholders prepare for cooperations with other key stakeholders? To this end, 20 qualitative interviews have been conducted with key stakeholders involved in emergency preparedness of SMRs, if introduced in the energy system. Preliminary results show that the actors have high expectations on SMRs. Geopolitical tensions, and conflict-related discourse—particularly regarding war preparedness—tend to overshadow consideration of radiological risks. Emergency preparedness and particularly radiological protection is projectizised, particularly by new stakeholders. Hence, a broad culture of preparedness involving early engagement of organizations and approaching radiological protection as an integral part of the strategic thinking around SMRs is missing so far. Radiological protection and emergency preparedness is merely seen as an activity that can be organised and structured later in the development process, and the implications of this need to be followed in the future.
Keywords: Emergency preparedness; Small Modular Reactors